Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Shareterhadap Keaktifan Belajar Pendidikan Agama Kristen dan Budi Pekerti Peserta Didik Kelas XI SMK N 1 Sigumpar Tahun Pembelajaran 2023/2024 - Samuelson Halomoan; Hasudungan Simatupang; Lustani Samosir (Universitas Katolik Widya Karya Malang, 2023)
The aim of this research is to determine the effect of implementing the Think Pair Share Type Cooperative Learning Model on the Learning Activeness of Christian Religious Education and Characteristics of Class XI Students at SMK N 1 Sigumpar in the 2023/2024 Academic Year. This research was carried out using quantitative methods, True experimental design in the form of Posttest-Only Control Design. The population is all class Data was collected by distributing questionnaires. The results of data analysis show that there is an influence of the application of the Think Pair Share Type Cooperative Learning Model on the Learning Activeness of Christian Religious Education and Characteristics of Class <Ltable(=0.05,n=15) = 0.220 and the experimental class obtained a value of Lcount=0.028<Ltabel(=0.05,n=15) =0.220. Thus it is known that the sample was taken from a normally distributed population. 2) Homogeneity test: obtained a value of Fcount=1.56<2.40, so the variance of the data analyzed is homogeneous. 3) Hypothesis test using the t test obtained tcount>ttable, namely 9.22>2.048, thus Ha is accepted and H0 is rejected. The implication of the results of this research is that the use/application of the Think Pair Share type cooperative learning model will increase students' active learning.